2015
DOI: 10.1007/s00464-015-4602-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating tactile feedback in robotic surgery for potential clinical application using an animal model

Abstract: Introduction The aims of this study were to evaluate 1) grasping forces with the application of a tactile feedback system in vivo 2) the incidence of tissue damage incurred during robotic tissue manipulation. Robotic-assisted minimally invasive surgery has been shown to be beneficial in a variety of surgical specialties, particularly radical prostatectomy. This innovative surgical tool offers advantages over traditional laparoscopic techniques, such as improved wrist-like maneuverability, stereoscopic video di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 28 publications
0
78
0
2
Order By: Relevance
“…To the best of our knowledge, despite a number of reports on perspective technologies,912,19,26 MTEC is currently the only commercially available medical device for intraoperative registration of tactile images. A previous study showed that for a simple testing stand, MTEC allowed correct localization of 95% of small heterogeneities (95% confidence interval for the correct detection rate: [0.83, 0.99]) 22.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, despite a number of reports on perspective technologies,912,19,26 MTEC is currently the only commercially available medical device for intraoperative registration of tactile images. A previous study showed that for a simple testing stand, MTEC allowed correct localization of 95% of small heterogeneities (95% confidence interval for the correct detection rate: [0.83, 0.99]) 22.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in this field showed that kinesthetic feedback provides a decrease of grasping force, which leads to lower tissue damage 19. However, design and implementation of diagnostic tactile feedback is still an open problem.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments comprised three blocks of peg transfer tasks performed by 20 subjects (4 surgeons), demonstrated a significant reduction of grip force during robotic manipulation with presence of tactile feedback in comparison with no-tactilefeedback interactions. In-vivo experimentation by 19 surgeons on porcine models for potential clinical implementation of tactile-feedback-equipped da Vinci robot was reported in [110]. The experiments demonstrated that tactile feedback significantly decreased grasping forces for both expert and novice surgeons.…”
Section: A General Minimally Invasive Surgerymentioning
confidence: 98%
“…The gripping torque τ s and the cylinder driving force f are obtained using the principle of virtual work, as follows: τs=r2xs2f=Jsf, where J s is the Jacobian of the gripping mechanism. According to the other researches, the required force for the grasping organ is about 3 N . Therefore, we set the maximum torque of the forceps to 80 mNm that is calculated by multiplying 3 N and the gripper length of 27 mm.…”
Section: Slave Forcepsmentioning
confidence: 99%